Cell-Free Expression to Probe Co-Translational Insertion of an Alpha Helical Membrane Protein - Blackholly, Laura R.; Harris, Nicola J.; Findlay, Heather E.; Booth, Paula J. (Frontiers in Molecular Biosciences, 2022)
The majority of alpha helical membrane proteins fold co-translationally during their synthesis on the ribosome. In contrast, most mechanistic folding studies address refolding of full-length proteins from artificially induced denatured states that are far removed from the natural co-translational process. Cell-free translation of membrane proteins is emerging as a useful tool to address folding during translation by a ribosome. We summarise the benefits of this approach and show how it can be successfully extended to a membrane protein with a complex knotted topology. The bacterial leucine transporter, LeuT can be synthesised and inserted into lipid membranes using a variety of in vitro transcription translation systems. Unlike major facilitator superfamily transporters, where changes in lipids can optimise the amount of correctly inserted protein, LeuT insertion yields are much less dependent on the lipid composition. The presence of a bacterial translocon either in native membrane extracts or reconstituted membranes also has little influence on the yield of LeuT incorporated into the lipid membrane. LeuT is considered a paradigm for neurotransmitter transporters and possesses a knotted structure that characteristic of this transporter family. This work provides a method in which to probe the formation of a protein with a knotted topology as the polypeptide chain is being synthesised on a ribosome and inserting into lipids. We show that in comparison with the simpler major facilitator transporter structure, LeuT inserts less efficiently into membranes when synthesised cell-free, suggesting that more of the protein aggregates, likely as a result of the challenging formation of the knotted topology in the membrane.